The Effect Of Project-Based Learning On Collaboration Skills Of High School Students - Muhamad Al Rasyid; Fitriah Khoirunnisa (JURNAL PENDIDIKAN SAINS (JPS), 2021)
The aimed of this study was to determine the collaborative skills of students in using project-based learning at SMAN 1 Tanjungpinang. The implementation of the project-based learning model was not optimally used during the learning process. This type of this research was quasi-experiment with pretest postest group design and data collection was carried out by distributing collaborative skills rubrics to 40 students, the sample was selected by purposive sampling technique. The data analysis technique used simple regression. The results showed that the students who have been taught by project-based learning had excellent collaborative skills and achieved good criteria of each indicator of collaboration skills.